Pengaruh Komunikasi Interpersonal dan Kompetensi Sumber daya terhadap Kinerja Guru dalam Penerapan Kurikulum Merdeka di SMPN 269 Jakarta - Azizah, Fitria Nur; Priyono, Totok (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study aims to identify the influence of Interpersonal Communication and Resource Competence on Teacher Performance at State Junior High School 269 Jakarta in implementing the independent curriculum. Interpersonal Communication barriers between Teachers and Students, as well as excessive teacher workloads, cause the technical performance of teachers to be the lowest among other performance areas. This study uses a descriptive approach to detail how Interpersonal Communication and Resource Competence affect Teacher Performance at State Junior High School 269 Jakarta in implementing the independent curriculum. Data were obtained through questionnaires and analyzed using Multiple Linear Regression with SPSS 26. The population consisted of principals, Teachers, Students, and Support Staff, with a sample of 222 respondents using proportional Stratified Random Sampling. The results of the study show that: (1) Interpersonal Communication has a positive but the lowest influence compared to other variables on Teacher Performance, with a t-test value of 15.124 > 1.971; (2) Resource Competence has a positive and dominant influence compared to other independent variables on Teacher Performance, with a t-test value of 20.282 > 1.971;(3) The combined influence of Interpersonal Communication and Resource Competence is 85.3%, with an f-test result of 161.646 > 3.04. The implications of this study suggest the need for balanced training on Interpersonal Communication and Resource Competence, focusing on effective Interpersonal Communication techniques and student-centered teaching strategies. Additionally, it highlights the importance of strong motivation from teachers to develop themselves post-training to avoid stagnation, thereby improving technical performance